Pemodelan Produk Domestik Regional Bruto di Indonesia dengan Regresi Nonparametrik Menggunakan Estimator Spline - Luh Putu Safitri Pratiwi; I Made Pasek Pradnyana Wijaya (Jurnal Statistika dan Aplikasinya, 2022)
The implementation of PPKM results in a decrease in community activities, hampers mobility and ultimately disrupts overall economic activity. So it is necessary to have a study that can explain the extent of economic development in Indonesia due to COVID-19 with a model. The modeling used in this research is nonparametric regression modeling with spline estimator. The purpose of this study is to determine the descriptive statistics of GRDP data in all provinces in Indonesia as an indicator of the rate of economic growth in Indonesia and to model the GRDP in Indonesia using nonparametric regression estimator spline. The results obtained in this study are the best nonparametric spline regression model with three knot points with a GCV value of 5199284230 and an R2 of 98.61 percent.